Effect of Entrepreneurial Marketing Strategies on Performance of Micro and Small Enterprises (MSEs) In Kenya - Kanake, Anne Muthoni; Karanja, Dr. Patrick Ngugi (Journal of Marketing Studies, 2018)
Purpose: Due to instability in the business environment organizations are forced to use approaches that are not standard. The study aimed at establishing the effect of EM strategies on performance of MSEs in Kenya. The study was guided by the following specific objectives; to explore the influence of Buzz marketing on performance of MSEs in Kenya, to ascertain the effect of Guerilla on performance of MSEs in Kenya, to determine the influence of new product marketing strategy on performance of MSEs in Kenya and to establish the impact of e-commerce on performance of MSEs in Kenya. Methodology: A descriptive survey design was adopted. The study targeted 20,000 MSEs. Managers were targeted in the MSEs. The study used a sample of three hundred and twenty nine. The sample was selected using simple random sampling. Semi-structured questionnaires were applied in gathering of data. The researcher administered the questionnaires to the respondents and research assistants helped in the task. Analysis of the data collected was performed using SPSS version 23. Descriptive statistics data analysis methods such as frequencies, means were applied to analyze numerical data gathered using closed ended questions. The study carried out a correlation analysis to measure the strength of the association of the variables being investigated. A multiple regression analysis was conducted to find how the study variables relate. Results: It was found that buzz marketing, guerilla marketing, new product marketing strategy and e-commerce marketing significantly and positively relate with performance of MSEs in Kenya. Recommendations: The study recommends management of MSEs to implement buzz marketing technique in their businesses this will help them overcome advertising clutter also the management should come up with different effective techniques that will create buzz in the market; MSEs should do their market research to help them come up with effective new product marketing strategies that will help them diversify target customer ranges and expand into new market segments especially before they introduce a new product to the market; and the government should have regular workshops where they teach MSE owners on various e-commerce and their advantages and also help them understand how they can apply them in their businesses.